The use of a high-fidelity simulation manikin in teaching clinical skills to fourth year undergraduate pharmacy students - Haddington, Nicholas; Hanning, Lyn; Weiss, Marjorie; Taylor, Denise (Pharmacy Education, 2013)
Background: A relatively new development in simulation-based teaching in healthcare education is the use of simulation manikins. While these have been used to teach clinical skills in various health disciplines, little has been reported on their use in UK undergraduate pharmacy programmes. Aims: To investigate the use of a simulation manikin to teach clinical skills to undergraduate pharmacy students. Method: A fourth year unit was developed to teach clinical skills to undergraduate pharmacists, including communication, consultation skills, clinical decision making and physical examination. A pre- and post-unit questionnaire was used to gather data relating to student confidence, self rated competence and student experience. Results: Student confidence and self-rated competence in key clinical skills increased significantly. High levels of acceptability for this teaching method were reported. Conclusion: This method of teaching clinical skills is effective and highly acceptable to undergraduate pharmacy students. Further research is necessary to compare this to other methods.